Analisis Lingkungan Sekitar Tambang Nikel Terhadap Kualitas Ternak Sapi Pedaging di Kabupaten Halamahera Timur - Gunawan, Gunawan; Priyanto, R.; Salundik, Salundik (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2015)
Continuous activity in nickel mining has resulted in steadily growing numbers of contaminants which influence the environment. Cattle rising nickel mining in East Halmahera are exposed to high contamination. This study was conducted to assess the presence of heavy metal contamination on soil, water, grass and animal products such as liver and meet. The method used were survey and case study. The parameters measured were the heavy metal content (Pb), Cadmium (Cd), Arsenic (As) and Mercury (Hg) in soil, water, grass and sample of cattle liver and meat. The samples were analyzed using AAS (Atomic Absorption Spectrophotometry) method. Thedata obtained were analyzed descriptively and t-test was used to asses the difference results of all parameters measured from two locations. The results showed that Pb in water and outside mining location were 0.1367 and 0.0770 ppm, respectively. Hg concentration in soil, water, grass, liver and meet callte raised around mining location were 17.8725, 0.0447, 6.6925, 7.4910 and 4.7210 ppb, respectively. The water around mining was contaminated with Pb. The contaminanion of Hg on soil, water and grass around mining areas, and also the liver and meat samples of cattle were exceeded the maximum standard that could be tolerated.Keywords: heavymetal,mining nickel,contamination, beef cattle.